Tax Competition under Minimum Rates: The Case of European Diesel Excises - Michiel Evers; Ruud A. de Mooij; Herman R.J. Vollebergh (Tinbergen Institute, 2004)
This paper estimates Nash-type fiscal reaction functions for European governments competing for revenue from diesel excises. It appears that European governments strategically set their excise levels by responding to their neighbors' tax rates. This provides evidence for the presence of tax competition in diesel excises. In fact, a 10% higher rate in neighboring countries (in terms of the user price) induces a country to raise its own rate by between 2 and 3%. This impact is robust for alternative specifications. By imposing restrictions on excise levels, EU harmonization of excises in 1987 and the introduction of a minimum in 1992 exerted a positive impact on the excise level in a number of EU countries. It has not, however, significantly reduced the intensity of tax competition. Indeed, strategic tax responses have not significantly been reduced by these harmonization policies. We also find that high-tax countries appear to compete more aggressively tha! n low-tax countries in the sense that they feature larger strategic tax responses. There is no significant difference between large and small countries.
Keywords: H23; H77; H87; R4; 330; Diesel excise; Strategic tax setting; Minimum rates; European Union; Dieselkraftstoff; Mineralölsteuer; Steuerwettbewerb; EU-Steuerrecht; Theorie; EU-Staaten